Stem cells for heart valve regeneration (Swiss Medical Weekly, 2012)
Heart valve tissue engineering holds the potential to overcome limitations of currently used heart valve prostheses. It involves the isolation and expansion of autologous patient cells, the subsequent seeding of these cells onto an appropriate scaffold material, the in vitro incubation and the in vivo implantation of the derived tissue-engineered construct into the patient from whom the cells were taken. While vascular-derived cells require harvest of intact donor tissue and show limited expansion capacities, the use of stem or progenitor cells may overcome these limitations and expand the versatility of the concept of heart valve tissue engineering. Possible sources include cells isolated from blood, bone marrow, adipose tissue, amniotic fluid, chorionic villi, umbilical cord and induced pluripotent stem cells. Here we review different stem cell sources with particular regard to cellular phenotypes and their suitability for application in heart valve tissue engineering.